2011
DOI: 10.2190/pm.42.2.a
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function and Medical Non-Adherence: A Different Perspective

Abstract: Medical non-adherence is multifactorial: cost, convenience, side effect profile, and cognitive impairment are all implicated in medical nonadherence. We explore impaired executive function (EF) as a cause for medical non-adherence when other causes can be ruled out. EF describes the coordination and manipulation of higher-order cognitive processes involved in problem-solving, planning, and decision-making. EF has three components: working memory, mental flexibility, and inhibitory control. The latter, inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
(30 reference statements)
2
21
0
Order By: Relevance
“…Several studies have reported significant relationships wherein impaired executive functions were found to be correlated with poorer quality of life, 9,43 less adaptive coping strategies, 9 poor social interactions, 44 academic difficulties, 37,39 and of particular interest for a CKD population, poor medical adherence. [28][29][30][31] The latter problems can result in increased health complications, worse health outcomes, and higher medical costs. 31 Adhering to the complex medical regimens often necessitated by CKD requires goal oriented behaviors, such as taking medications as prescribed, coordinating multiple doctors' appointments, and implementing lifestyle changes (e.g., dietary restrictions), all of which require planning, organization, and inhibitory control for prioritizing long-term health benefits over short-term gratification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported significant relationships wherein impaired executive functions were found to be correlated with poorer quality of life, 9,43 less adaptive coping strategies, 9 poor social interactions, 44 academic difficulties, 37,39 and of particular interest for a CKD population, poor medical adherence. [28][29][30][31] The latter problems can result in increased health complications, worse health outcomes, and higher medical costs. 31 Adhering to the complex medical regimens often necessitated by CKD requires goal oriented behaviors, such as taking medications as prescribed, coordinating multiple doctors' appointments, and implementing lifestyle changes (e.g., dietary restrictions), all of which require planning, organization, and inhibitory control for prioritizing long-term health benefits over short-term gratification.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, for the individual with CKD, poor executive functioning can contribute to difficulty in keeping doctors' appointments, following dietary recommendations, and remembering to take medications. [28][29][30][31] This nonadherence not only increases the risk of medical complications and hospitalizations for the child, adolescent, or young adult with CKD but also has the potential to increase the financial burden to patients, their families, insurance companies, and public assistance programs. 31 However, the directionality of this relationship remains unknown.…”
mentioning
confidence: 99%
“…It is likely that executive dysfunction impairs the ability of patients to adhere to medical recommendations and follow-up. 54 …”
Section: The Brain In Children and Adolescents (Figures 3 And 4)mentioning
confidence: 99%
“…[3][4][5][6][7] The primary neuropsychological impairment in OCD lies in executive functions such as working memory, cognitive flexibility, and response inhibition. 5,8,9 These deficits have been hypothesized to mediate the relationship between brain dysfunction and clinical symptomatology in patients with OCD. 10 This observation is supported by studies which show a direct relationship between anterior cingulate (ACC) activity and cognitive control, since the conflict-monitoring processes in the ACC appear to be involved in the engagement of this cognitive ability.…”
Section: Introductionmentioning
confidence: 99%